T cell PTLD successfully treated with single-agent brentuximab vedotin first-line therapy - Choi, Mira; Delecluse, Susanne; Prasad, Vikas; Anagnostopoulos, Ioannis; Reinke, Petra; Schmitt, Clemens Alexander (Transplantation, 2016)
An abstract is unavailable.
Gesehen am 04.05.2020